An acetylation site in the middle domain of Hsp90 regulates chaperone function - Scroggins, Bradley T; Robzyk, Kenneth; Wang, Dongxia; Marcu, Monica G; Tsutsumi, Shinji; Beebe, Kristin; Cotter, Robert J; Felts, Sara; Toft, David; Karnitz, Larry; Rosen, Neal; Neckers, Len (Molecular cell, 2007)
Heat-shock protein 90 (Hsp90) chaperones a key subset of signaling proteins and is necessary for malignant transformation. Hsp90 is subject to an array of posttranslational modifications that affect its function, including acetylation. Histone deacetylase (HDAC) inhibitors and knockdown of HDAC6 induce Hsp90 acetylation and inhibit its activity. However, direct determination of the functional consequences of Hsp90 acetylation has awaited mapping of specific sites. We now demonstrate that Hsp90 K294 is acetylated. Mutational analysis of K294 shows that its acetylation status is a strong determinant of client protein and cochaperone binding. In yeast, Hsp90 mutants that cannot be acetylated at K294 have reduced viability and chaperone function compared to WT or to mutants that mimic constitutive acetylation. These data suggest that acetylation/deacetylation of K294 plays an important role in regulating the Hsp90 chaperone cycle.